Immune Thrombocytopenia Plasma-Derived Exosomes Impaired Megakaryocyte and Platelet Production through an Apoptosis Pathway - Miao, Wenjing; Song, Baoquan; Shi, Bingyu; Wan, Qi; Lv, Quansheng; Chen, Hanqing; Zhu, Mingqing; Zhang, Leisheng; Han, Yue; Wu, Depei (Thrombosis and Haemostasis, 2020)
Reduced megakaryocyte (MK) apoptosis and insufficient platelet production play important roles in the pathogenesis of immune thrombocytopenia (ITP). The contribution of plasma-derived exosomes to the decreased platelet count in ITP has not been entirely understood. Here, we found the percentage of apoptotic MKs in patients with ITP was significantly lower than those in healthy volunteers. In the presence of ITP plasma-derived exosomes (ITP-Exo), the apoptosis of MKs was reduced during the process of MK differentiation in vitro, which contributed to the reduced platelet production by Bcl-xL/caspase signaling. Furthermore, in vivo study demonstrated that ITP-Exo administration led to significantly delayed platelet recovery in mice after 3.5 Gy of irradiation. All these findings indicated that ITP-Exo, as a regulator of platelet production, impaired MK apoptosis and platelet production through Bcl-xL/caspase signaling, unveiling new mechanisms for reduced platelet count in ITP.
Keywords: immune thrombocytopenia; exosomes; megakaryocyte; platelets; apoptosis